Day-ahead planning optimization framework for cascaded hydro-wind-photovoltaic hybrid systems considering time delay effects - Zhiyuan Wu; Haizheng Wang; Guohua Fang; Jian Ye; David Z. Zhu; Xianfeng Huang (International Journal of Electrical Power & Energy Systems)
The time delay in cascade hydropower stations refers to the time required for water to travel from the upstream reservoir to the downstream reservoir. Although some studies consider time delays in hydro-wind-photovoltaic hybrid system models, comprehensive research on their impacts and mitigation strategies remains limited. These delays hinder the joint optimization of hydropower, wind, and photovoltaic resources, reducing system benefits and increasing operational risks. This phenomenon is referred to as the time delay effect. This study proposes a day-ahead planning optimization framework to mitigate the time delay effect and improve system benefits and reliability under multiple uncertainties. This framework incorporates joint and updated optimizations to address challenges posed by the time delay effect. A case study on the Yalong River Basin hydro-wind-photovoltaic system shows that the proposed framework enhances generation benefits by 2.79% over traditional methods and reduces the power shortage rate by 43.19%. Additional multi-objective scheduling experiments assess the framework’s risk control capabilities and the variations in scheduling across different schemes. Based on these analyses, an improvement strategy for this system is developed and validated to significantly reduce power shortage rates while minimizing revenue losses.